Analysis of Consumer Experience, Consumer Engagement, and E-Wom in Improving Consumer Satisfaction in Purchasing Wuling Spare Parts at Lesmana Motor - M. Yusran; Elfitra Desy Surya; Erwansyah Erwansyah (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of consumer experience, consumer involvement, and e-WOM on consumer satisfaction when purchasing Wuling spare parts at Lesmana Motor using quantitative methods and a sample of 85 respondents. The partial test results indicate that consumer involvement has a positive and significant effect (sig. 0.024 < 0.05), while consumer experience (0.333 > 0.05) and e-WOM (0.934 > 0.05) are insignificant.Simultaneously, all three variables have a significant effect (F-test 95.025; sig. 0.000 < 0.05). The coefficient of determination (R) of 0.492 indicates that 49.2% of the variation in consumer satisfaction is explained by the model, while 50.8% is influenced by other factors. In conclusion, consumer involvement is a major factor in increasing consumer satisfaction.